A serotype 10 human rotavirus. - Beards, G (1992)
Rotaviruses with genome rearrangements isolated from a chronically infected immunodeficient child (F. Hundley, M. McIntyre, B. Clark, G. Beards, D. Wood, I. Chrystie, and U. Desselberger, J. Virol 61:3365-3372, 1987) are the first recognized human isolates of serotype 10. This was shown by both a direct enzyme-linked immunosorbent assay and virus neutralization assays using serotype specific monoclonal antibodies. The serotype was confirmed by sequence analysis of the gene encoding VP7, which revealed a 96% amino acid homology to the bovine serotype 10 isolate B223.